دلالة مفهوم النص عند الأصوليين مفهوم العدد أنموذجاً ((دراسة مقارنة بالقانون العراقي)) - حسين شذى مظفر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research presents a comparative study between Islamic jurisprudence and Iraqi law regarding the concept of numerical indication and its implications in texts. It focuses on analyzing how legal and Shari’a rulings are derived from texts containing numbers, and it highlights the points of similarity and difference between the two approaches. The research is divided into three sections. It concludes that Islamic jurisprudence is characterized by flexibility in interpreting numbers based on the objectives of Shari’a, whereas Iraqi law tends to adopt strictness to avoid ambiguity in legal texts.